Single-source precursor-based deposition of Sb2Te3 films by MOCVD - Bendt, Georg; Schulz, Stephan; Zastrow, Sebastian; Nielsch, Kornelius (Chemical Vapor Deposition, 2013)
The low-temperature metal-organic (MO)CVD of Sb2Te3 films is achieved by the use of the single-source precursor (Et2Sb)2Te, 1. The role of the substrate temperature on the deposition rate and the composition of the resulting film is described. The resulting Sb2Te3 films are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) and Auger spectroscopies. Moreover, the Seebeck coefficient of the Sb2Te3 film deposited at 200 °C is determined, and the value of 160µVK-1 demonstrates the high quality and low carrier density of the film.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Sb; Seebeck coefficient; Single-source precursor; Thermoelectric; Thin film